Acute embryotoxic effects but no long‐term reproductive effects of in ovo methylmercury exposure in zebra finches (Taeniopygia guttata). (29th March 2016) - Yu, Maria S.; Eng, Margaret L.; Williams, Tony D.; Basu, Niladri; Elliott, John E.
Abstract: Mercury bioaccumulates in terrestrial ecosystems as methylmercury (MeHg), yet little is known about its effects on terrestrial organisms, including songbirds. The authors used a model songbird species, the zebra finch ( Taeniopygia guttata ), to assess short‐term embryotoxic effects of in ovo MeHg exposure on hatching success and posthatching growth and nestling survival, as well as longer‐term effects on mating behavior and reproduction. Egg treatment groups included a low‐MeHg dose of 0.2 μg Hg g −1 egg ( n  = 36), a high‐MeHg dose of 3.2 μg Hg g −1 egg ( n  = 49), and a control ( n  = 34). Doses were dissolved in nanopure filtered water and injected into the albumen on the day eggs showed signs of viability (3 d incubation). In ovo exposure to MeHg significantly reduced hatching success (53% in the high‐MeHg dose group vs 94% in vehicle controls). Among hatched chicks, however, no effects of MeHg on growth, hematological variables, or nestling survival were detected. While the in ovo injection method resulted in a dose‐dependent pattern of MeHg concentrations in blood of surviving chicks at 15 d and 30 d posthatching, there was evidence of rapid excretion of MeHg with nestling age during that growth period. At reproductive maturity (90 d of age), no long‐term effects of in ovo exposure to MeHg on female mating behavior, reproductive effort (egg or clutch size), or growth and survivorship of offspring were observed. Environ Toxicol Chem 2016;35:1534–1540. © 2015 SETAC